Morphocytometric Evaluation of Equine Oocytes Following In Vitro Maturation - Hussam ARYAN; Omar MARDENLI; Ioan GROZA (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Veterinary Medicine, 2023)
In the current study, 930 equine oocytes were collected, 765 (82.25%) of which were considered viable for in vitro maturation. All selected oocytes were matured for 27 h at 38.50 0C in an atmosphere of 5% CO2 in humidified air. 25 mm hepes-buffered TCM-199 supplemented with 2 mm sodium pyruvate, 1mm l-glutamine, penicillin (75 mg/ml), streptomycin (50 mg/ml) and 10% fetal calf serum was used for in vitro maturation. Following maturation, matured COCs were examined to investigate for first polar body formation. The morphocytometric assessment was performed using the motic image plus (MIP) software with an inverted microscope. Morphocytometric examination results showed highly significant differences (p<0.001) among groups of matured oocytes (zona pellucida thickness; <13 µm, cumulus oophorus thickness; < 10 µm and oocytes diameter; < 100 µm), where the rates were 63.39%, 33.59% and 30.58%, respectively. The results of morphocytometric evaluation based on zona pellucida thickness, cumulus oophorus thickness and oocyte diameter of the total 765 cultured oocytes showed that 197 oocytes (25.75%) were classified as excellent mature, 108 oocytes (14.11%) as mature good, 203 oocytes (26.53%) as immature and 257 oocytes (33.59%) were considered as degenerated. It is concluded thatthe oocytes rates differed according to the parameters (cumulus oophorus, oocytes diameter, zona pellucida).